Daily reciprocal relations between emotion dysregulation and non‐suicidal self‐injury among individuals with a history of sexual assault: The influence of posttraumatic stress symptoms. Issue 1 (3rd November 2022) - Raudales, Alexa M.; Yang, Manshu; Schatten, Heather T.; Armey, Michael F.; Weiss, Nicole H.
Abstract: Introduction: Non‐suicidal self‐injury (NSSI) is a serious public health concern that can be understood within an emotion dysregulation framework. The current study adds to the literature by utilizing a micro‐longitudinal design and novel statistical modeling to test reciprocal associations between emotion dysregulation and NSSI, as well as the potential moderating effect of posttraumatic stress symptoms (PTSS). Methods: Participants were 81 individuals with a history of sexual assault and NSSI ( M age  = 33.80; 67.9% women; 80.2% white) recruited from the community who self‐reported on symptoms of emotion dysregulation and NSSI thoughts/behaviors once daily for 7 days. Average compliance rate was 72.8% (SD = 31.3%) and 34 participants (42.0%) endorsed NSSI thoughts/behaviors over the course of the study. Results: Findings revealed a significant positive effect of NSSI thoughts/behaviors on subsequent abilities to regulate negative emotions. Furthermore, while results did not detect a moderating influence of baseline PTSS on the relation between emotion dysregulation and NSSI thoughts/behaviors over time, individuals with higher baseline PTSS were found to experience heightened levels of NSSI thoughts/behaviors and emotion dysregulation on average. Conclusion: Information from this study may be useful for future research and intervention development focused on the intersection of NSSI, PTSS, and emotion dysregulation.